Assessment of Business Education Physical Learning Resources for The Implementation of Activity-Based Learning in Bauchi State Colleges of Education - Gambo, , Kulu; Hamisu, M.; B. Abdulmutalib, Umar, (Kashere Journal of Education, 2021)
The study assessed business education physical learning resources with a view to be upgraded to support the use of Activity-based learning strategy in Bauchi state colleges of education. Two objectives and two research questions were formulated. Survey design was adopted. The population of the study was 36 business educators from colleges of education Azare and Adamu Tafawa Balewa college of education Kangere. Total population sample was used in the study. The instrument used for data collection was Business Education Resource Upgrade Questionnaire. Data were analyzed using mean and standard deviation. The study revealed that physical facilities were moderately upgraded to support the use of the Activity-based learning strategy at COE, Azare and ATBCOE, Kangere. Also, equipment and supplies were less upgraded in COE Azare and ATBCOE, Kangere to support the use of Activity-based learning strategy. It was recommended that management of COE Azare should strive through public-private partnership with industries, philanthropist, international donor agencies and their internally generated revenue for sustainability to keep the program up-to-date to the tune of time. Bauchi state government should also partner for additional funding in addition to internally generated revenue from ATAP and ATBCOE in order to provide them with adequate physical facilities, equipment supplies and consumables for business education program effectiveness in order to successfully implement Activity-based learning strategy in the school.